Manajemen Laba Terhadap Nilai Perusahaan Pada Pergantian CEO - Wijaya, Dwi Cahyadi Tantra; Budiasih, I G.A.N. (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p02, 2018)
The purpose of this study was to determine the effect of earnings management on firm value with income increasing patterns at the end of old CEO position and income decreasing patterns at the beginning of new CEO position in companies that are listed on the Indonesia Stock Exchange (IDX). This research conducted on companies listed on the Stock Exchange in 2010 - 2017. Samples in this study were 45 companies in observation of the old CEO position and 54 companies in observation of the new CEO position obtained by purposive sampling method. The data analysis technique used is simple linear regression. The results show that earnings management with income increasing patterns at the end of the year of CEO's position, and earnings management with income decreasing patterns at the beginning of new CEO's position negatively affects firm value. Keywords : Firm value, earnings management, CEO turnover, income increasing, income decreasing.